PEMBUATAN DOKUMEN PERANCANGAN INDUSTRI KECIL PENGOLAHAN BONGGOL JAGUNG BAGI PETANI JAGUNG RACAKALONG, SUMEDANG, JAWA BARAT - Hendang Setyo Rukmi; Andry Masri (LP4MK STKIP PGRI Lubuklinggau, 2022)
Sumedang Regency is known as one of the important corn production center in West Java province. Utilization of corn cobs is needed to improve the local economy and minimize corn harvest waste which could provide added value for the community. Community service was carried out to create a small industry design document for corn cob processing for corn farmers to be established in the Rancakalong Region, Sumedang Regency. The small industry design document for corncob processing covers marketing aspects, human resources aspects, technical aspects, legal and environmental aspects, and financial aspects. This document is very much needed by the community as a reference in minimizing the risk of establishing a small corncob processing industry. This project is part of the Matching Fund program from the Ministry of Education and Culture of the Republic of Indonesia under the Kedaireka platform which is based on the results of research on the establishment of a small corncob processing industry in Bandung.